Pengaruh Kelengkapan Handrub & Poster terhadap Kemauan Perawat untuk Berubah Terkait Hand Hygiene pada Rawat Inap RS Ananda Blitar - Pratama, Bramantya Surya; Koeswo, Mulyatim; Hariyanti, Tita (Universitas Brawijaya, Indonesia, 2016)
Hospital-acquired infections (HAI) are infections that occur in healthcare while undergoing treatment procedures and medical treatment. HAI causes elongation of hospitalization, do harm to the patient and increases maintenance costs. The most effective way to limit the spread of HAI is to implement hand hygiene by the rules. The results of preliminary study in Ananda Hospital Srengat Blitar found that nosocomial infection rates is high (infusion phlebitis incident is 12.4%) and nurses hand hygiene compliance is low (hand hygiene compliance is 26%). The purpose of this study was to find the relationship between the completeness of handrub and posters on the nurses's intention to change to perform hand hygiene correctly. The research method is use the design explanatory research with cross sectional approach. The results showed that the completeness of handrub clinically significant influence intention to change to perform hand hygiene (P = 0.000), while between the poster and the intention to change had effect but not significant (P = 0.128) and completeness of handrub and posters simultaneously significant effect on the intention to change (P = 0.000). This study can be concluded that the completeness of handrub and posters are a combination that can help to increase the nurse's intention to change to perform hand hygiene than partially effect.Â